Care-seeking behavior and out-of-pocket expenditure for sick newborns among urban poor in Lucknow, northern India: a prospective follow-up study - Srivastava Neeraj M; Awasthi Shally; Agarwal Girdhar G (BMC, 2009)
Abstract Background The state of Uttar Pradesh, India accounts for one-quarter of India's neonatal deaths and 8 percent of those worldwide. More than half (52%) of these deaths occur due to infections. In order to achieve Millennium Development Goal-4 of reducing child mortality by two-thirds by the year 2015, it is important to study factors which affect neonatal health. In Uttar Pradesh there is meager data for spending on health care in general and neonates in particular. Methods The study was conducted at an urban Reproductive and Child Health (RCH) center and a District hospital. Neonates were enrolled within 48 hours of birth and were followed-up once at 6 weeks ± 15 days at the OPD of the respective hospitals or at home. This study assessed (1) distribution of neonatal illnesses and different health providers sought (2) distribution of out-of-pocket expenditures by type of illness and type of health provider sought (3) socio-economic distribution of neonatal illnesses, care-seeking behavior and out-of-pocket expenditures. Per-protocol analysis was performed. Results Five hundred and ten neonates were enrolled and 481(94.4%) were followed-up. Parents of 50.3% (242/481) neonates reported at least one symptom of illness. Of these 22.3% (107/481) neonates had illnesses with at least one reported Integrated Management of Neonatal and Childhood Illnesses (IMNCI) danger sign. Among IMNCI illnesses, point prevalence of septicemia was 6.2% and pneumonia was 5.2% while among non-IMNCI illnesses point prevalence of upper respiratory infection was 9.5%, and diarrhea was 7%. Community based non-government dispensers (NGDs) were leading health providers (37.6%). Mean monthly income of families was 2804 Indian Rupees (INR) (range: 800 to 14000; n = 510), where US$ 1 = 42 INR. Mean out-of-pocket expenditure on neonatal illness was 547.5 INR (range: 1 to 15000; n = 202) and mean out-of-pocket expenditure for hospitalization was 4993 INR (range: 41 to 15000; n = 17). All hospitalizations were for IMNCI illnesses. Neonates from lower income strata were less likely to receive any medical care (p < 0.0001) and were also less likely to be seen by a Government provider (p = 0.03). Conclusion Since more than half of the neonates have morbidity and out-of-pocket expenditure on neonatal illnesses often exceeds the family income of the lower strata of the low income group in the community, there is a need to either introduce health insurance scheme or subsidize health care for them. Also, since NGDs, half of which could be unqualified are leading health providers, qualified medical care-seeking for sick newborns should be promoted in urban Lucknow.